Fourier transform infrared spectroscopy on cooking oils - Lin, Dennis Shirong. (2013)
The purpose of this study is to optimize and characterize the cooking oils using Fourier Transform Infrared Spectroscopy (FTIR) in combination with the help of multivariate tool, Principal Component Analysis (PCA). Six cooking oils were purchased for this project.